Reflections on the relational ontology of medical assistance in dying - Pesut, Barbara; Thorne, Sally (2023)
Canadian nursing practice has been profoundly influenced by the legalization of medical assistance in dying in 2016, requiring that nurses navigate new and sometimes highly challenging experiences. Findings from our longitudinal studies of nurses' experiences suggest that these include deep emotional responses to medical assistance in dying, an urgency in orchestrating the perfect death, and a high degree of relational impact, both professionally and personally. Here we propose a theoretical explanation for these experiences based upon a relational ontology. Drawing upon the work of Wildman, we understand a relational ontology to be one in which relationships are more fundamentally central than the conceptual entities that provide the context to practice. It is in a relationship that conceptual entities, and their affiliated values, are created and recreated. Seen as causal, relationships have ontological status, with important implications for how we consider the concepts of death, suffering, and time in this context. From a conceptual perspective, suffering is primarily self-defined based upon personal histories, time reflects the potential remaining until death, and death is primarily biological and amoral, although social discourses of a good and bad death surround the death trajectory. However, within a relational ontology of medical assistance in dying, these understandings shift. Death becomes primarily social rather than biological, suffering is shared, and time until death is now clearly delimited. Accordingly, nurses assume a profound responsibility for influencing outcomes that are authentically person-centered. These understandings provide important insights into nurses' experiences, enabling us to recognize the causal effects, both intended and unintended, of nurses' relational practices amidst the complexities of assisted death. Drawing on such a perspective, we find implications for how we provide spaces for nurses to reflect on, and have conversations about, their experiences with some of the greatest mysteries of life—death, suffering, and time.
Keywords: relational practice; nurses' experience; Morality; medical assistance in dying; Euthanasia; Ethics